2018
DOI: 10.1007/s10499-018-0305-8
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing metamorphosis in Paracentrotus lividus aquaculture using alternative macroalgae species to Corallina sp.

Abstract: Metamorphosis induction cues (by chemical mediation or direct contact) were tested in Paracentrotus lividus using three different macroalgae treatments: Corallina sp., Palmaria palmata and Laminaria digitata. Higher percentages of metamorphosis were reached in Paracentrotus lividus larvae by direct contact with a Palmaria palmata substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
(24 reference statements)
1
7
2
Order By: Relevance
“…It was then verified that feeding with a mixture of microalgae (D3) allowed a survival significantly higher than the other treatments, possibly due to the nutritive quality of the conjugation of the two microalgae tested. The survival of the postlarvae of treatment D3 was very similar to the results obtained byBrundu et al (2016), being even higher than those obtained byCastilla-Gavilán, Buzin, et al (2018a);Castilla-Gavilán, Turpin, et al (2018b). The high survival rate may have been due to the good nutritive quality of the conjugation of the two microalgae combined with the good stimulation of the settlement substrates used, namely the quality of the organic metabolites and bacterial biofilm present in the substrates used, factors essential to the success of substrate fixation and metamorphosis(Dworjanyn & Pirozzi, 2008).In conclusion, like in other similar studies, the use of diversify microalgae specie diets has a great positive influence on the success of the development and survival of P. lividus larvae.…”
supporting
confidence: 83%
See 3 more Smart Citations
“…It was then verified that feeding with a mixture of microalgae (D3) allowed a survival significantly higher than the other treatments, possibly due to the nutritive quality of the conjugation of the two microalgae tested. The survival of the postlarvae of treatment D3 was very similar to the results obtained byBrundu et al (2016), being even higher than those obtained byCastilla-Gavilán, Buzin, et al (2018a);Castilla-Gavilán, Turpin, et al (2018b). The high survival rate may have been due to the good nutritive quality of the conjugation of the two microalgae combined with the good stimulation of the settlement substrates used, namely the quality of the organic metabolites and bacterial biofilm present in the substrates used, factors essential to the success of substrate fixation and metamorphosis(Dworjanyn & Pirozzi, 2008).In conclusion, like in other similar studies, the use of diversify microalgae specie diets has a great positive influence on the success of the development and survival of P. lividus larvae.…”
supporting
confidence: 83%
“…The use of the species Rhodomonas spp. in sea urchin larvae feeding has been previously studied by some authors such as Hubbard, Wolcott, and Baca (2003), Wolcott and Messing (2005), Castilla-Gavilán, Buzin, et al (2018a);Castilla-Gavilán, Turpin, et al (2018b), and in general, good results have been observed. The use of S. costatum on P. lividus rearing has not been described yet.…”
Section: Feedingmentioning
confidence: 92%
See 2 more Smart Citations
“…In the last years, several microalgae species have been tested to optimize the larvae culture, such as the genus Isochrisis aff. Galbana , Dunaliella , Rhodomonas , Chaetoceros calcitrans , Tetraselmis suecica , Nannochloropis oculate (Ahmed et al, 2016; Carboni et al, 2012; Castilla‐Gavilán, Buzin, et al, 2018; Castilla‐Gavilán, Turpin, et al, 2018). Some benthic diatoms, such as Cocconeis scutellum parva , Diploneis sp., Navicula incerta , Cylindrotheca closterium and Nanofrustulum shiloi were also tested to improve settlement success (Zupo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%